GC-MS-based identification and statistical analysis of liposoluble components in the rhizosphere soils of Panax notoginseng. Issue 36 (2nd July 2019) - Qiao, Yi-Jun; Zhang, Jia-Jiao; Shang, Jia-Huan; Zhu, Hong-Tao; Wang, Dong; Yang, Chong-Ren; Zhang, Ying-Jun
Abstract : Liposoluble components in the rhizosphere soils of Panax notoginseng were found as potential allelochemicals by GC-MS identification and statistical analysis. Abstract : Continuous cropping obstacle, mainly caused by microorganisms and organic components in soil, has become a serious problem for the plantation of Panax notoginseng (Araliaceae) due to the rapidly increased demands of this famous herbal medicine in recent decades. The rhizosphere soils cultivated with 3-year-old healthy and ill notoginseng were chemically investigated by gas chromatography-mass spectrometry (GC-MS) and compared with the corresponding soils without the plantation of notoginseng. Totally 47 liposoluble components were identified. Furthermore, the multiple statistical analysis showed that these constituents were qualitatively and quantitatively associated with the differences between the cultivated soil with P. notoginseng and the uncultivated soil. Among them, neophytadiene (4 ), d -α-tocopherol (38 ), (3β, 22 E, 24 S )-ergosta-5, 22-dien-3-ol (39 ), (3β, 24 R )-ergost-5-en-3-ol (40 ), stigmasta-5, 22-dien-3-ol (41 ), stigmast-4-en-3-one (44 ) and (5α)-stigmastane-3, 6-dione (47 ) contributed most to the significant differences between the cultivated and uncultivated soils, whereas cyclopentadecane (3 ), octadecanoic acid methyl ester (16 ), docosanoic acid ethyl ester (31 ), nonacosane (34 ), 38 and39 were found in much higher amount in the soils with ill P. notoginseng as compared to the case of those with the healthy P. notoginseng . On the other hand, liposoluble components in different cultivation areas were of great diversity; however, they were able to remain relatively consistent across the overall trend of differential substances.